Virtual Reality-Based Hajj Manasik Practice Digitization System with 360 Degree Video - Hanrian Rossa; Noor Hudallah; Budi Sunarko; Anggraini Mulwinda (Budapest International Research and Critics University, 2022)
Hajj guidance is a simulation activity carried out by pilgrims so that pilgrims can better prepare themselves. Even though they have carried out the guidance for Hajj, sometimes the congregation still feels that they do not understand the material they are learning and feel that they have not learned enough about the object of Hajj by using guide books, especially the practice of the Hajj. But pilgrims have not taken the guidance of other Hajj because of the cost, time and place they need. By using virtual reality based on 360-degree videos, pilgrims can understand the material better and can perform the pilgrimage independently without being hindered by time, place and cost. The research was conducted using Research and Development (R&D) research methods and then using a quantitative approach to approach the application. The instruments used in this research include material expert test sheets, media test sheets, and user usability test sheets. The results show that virtual reality (VR) based on 360-degree video is a media that is feasible to use and has very good benefits for prospective pilgrims.